2003
DOI: 10.1016/s0014-5793(03)00400-9
|View full text |Cite
|
Sign up to set email alerts
|

Short interfering RNA‐directed inhibition of hepatitis B virus replication

Abstract: RNA interference (RNAi) is the process by which double-stranded RNA directs sequence-speci¢c degradation of mRNA. In mammalian cells, RNAi can be triggered by 21-nucleotide duplexes of short interfering RNA (siRNA). We examined e¡ects of siRNA on hepatitis B virus (HBV) replication. Human hepatoma cells were transfected with HBV DNA and siRNA against HBV-pregenome RNA. Transfection experiments demonstrated that the siRNA reduced the amount of HBV-pregenome RNA and resulted in reduction of the levels of replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 21 publications
2
80
0
Order By: Relevance
“…ported. [35][36][37] We have shown here that siRNA targeted against a specific sequence in the HBV genome can inhibit HBV replication, resulting in decreased amounts of HBV protein in cells and medium using a stable HBV-producing cell line. The HepG2 2.2.15 system was selected as a model because the production of virus is constitutive, and levels of RNA and antigens are stable.…”
Section: Discussionmentioning
confidence: 91%
“…ported. [35][36][37] We have shown here that siRNA targeted against a specific sequence in the HBV genome can inhibit HBV replication, resulting in decreased amounts of HBV protein in cells and medium using a stable HBV-producing cell line. The HepG2 2.2.15 system was selected as a model because the production of virus is constitutive, and levels of RNA and antigens are stable.…”
Section: Discussionmentioning
confidence: 91%
“…Knock-down of HBx expression by si-or sh-RNA methods has been reported to down-regulate HBV transcription and replication. (67)(68)(69) Down-regulation of HBx might reduce HBV gene expression and replication and might also reduce the ability to overcome OIS. It is natural to expect that HBV replication and tumorigenic incidence would be reduced or prevented by the knock-down of HBx or by specific inhibitors of HBx.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, there is a need for alternative ways to treat this persistent infection. RNA interference (RNAi) has rapidly emerged as a technology for regulating mammalian gene expression because it provides a means of sequence-directed degradation of specific RNAs (1)(2)(3)(4)(5)(6)(7)(8). In the case of HBV, published in vivo hydrodynamic transfection studies have shown that simultaneous delivery of HBV expression plasmids and HBV-specific small interfering RNAs (siRNAs) (or siRNA-expressing constructs) to the mouse liver can prevent the induction of HBV gene expression and replication (9)(10)(11).…”
mentioning
confidence: 99%